China's urban gender wage gap: A new direction? - Jin Song; Terry Sicular; Björn Gustafsson (The University of Western Ontario, Centre for Human Capital and Productivity (CHCP), 2017)
Using data from the urban household surveys of the China Household Income Project for the years 1995, 2002, 2007 and 2013, we provide consistent estimates of the gender wage gap in urban China and investigate those factors that have contributed to this gap. Similar to past studies, we find a substantial and progressive widening of the gap from 1995 to 2007. Based on new data for 2013, however, we find that from 2007 to 2013 the gender wage gap narrowed. For 2013 we estimate the gender wage gap at between 19 percent and 25 percent. Oaxaca-Blinder decompositions reveal that the contributions of the differences in characteristics between women and men to the wage gap declined over time, and by 2013 the gap is largely unexplained. We identify key factors underlying the gender wage gap in recent years, specifically, individual characteristics, such as age, education, marriage, and children, as well as employment sector and occupation.
Keywords: J16; J31; O15; P23; 330; China; urban; inequality; gender; wage gap